Estimation of the Salivary Iron in Children with Dental Caries: A Pilot Study - Brunah de Oliveira BUCHE; Bruno GUSSO; Fernanda Mara de Paiva BERTOLI; Juliana Feltrin de SOUZA; Ana Tereza Bittencourt GUIMARÃES; João Armando BRANCHER (Tehran University of Medical Sciences, 2016)
Estimation of the Salivary Iron in Children with Dental Caries: A Pilot Study